Current law legislation citator 1986 : statutes 1972-86 statutory instruments affected 1947-86 (London : Sweet & Maxwell, 1987)
This Statute Citator is cumulative for the period 1972-86; for previous amendments consult the 1971 Statute Citator which consolidates the amendments for period 1947-71.
usc 28/01/2019
Loans
Keywords: Annotations and citations (Law); Law; Great Britain